Tiny house design proposal / Aimi Syamimi Azman - Azman, Aimi Syamimi (Universiti Teknologi MARA UiTM,Perak, 2022)
In semester 7, students of Bachelor in Building Surveying are required to completing Industrial Training at any firm or company that related with syllabus in Building Surveying to gain experience in building development industry. The aims of this Practical Training is to develop intellectual, powers and ability of students in analyzing fact finding and investigation through relevant scientific and qualitative analysis. It is to educate the student in dealing with the implication of developments and awareness of factors affecting the built environment and society. Students also need to prepare a report that related with the industrial training and require the Department’s approval of the topic. The topic of this report is Tiny House Design Proposal.